Temperature control response using fuzzy PI+PID controller / Adham Mohd Norhamizi - Mohd Norhamizi, Adham (2017)
The aim of this project is to evaluate the process performance of temperature control process using combination of Fuzzy PI and PID. In this work, the experimental data is used to determine the process model and the control analysis is done using LabVIEW software. The PID control was tuned by using Ziegler-Nichols method and the Fuzzy PI controller are design with different sets of membership functions. The performance of the output response is evaluated and compared in term of settling time, rise time and percent overshoot. The result had shown that the performance with 7 membership function gives better performance for temperature control process.